Effect of Itrifal Muqawwi-e-Dimagh (a polyherbal drug) on the transgenic Drosophila model of Parkinson's Disease - Yasir Hasan Siddique; Falaq Naz; Rahul; Mohammad Rashid; Shariq Mian (Elsevier, 2021)
Background: Parkinson's Disease (PD) is characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta of the mid brain which leads to the depletion of dopamine levels. The depletion of dopamine leads to the motor dysfunction characterized by tremors, rigidity, bradykinesia and postural instability. In this context, the effect of unani herbal formulation Itrifal Muqawwi-e-Dimagh (IMD) was studied on the transgenic Drosophila melanogaster expressing human alpha synuclein in the neurons of flies. IMD is recommended for enhancing mental power and to treat mental illness in the Unani system of medicine. IMD was prepared as per the standard procedures and was subjected to various physico-chemical tests. Methods: The equivalents of recommended dose for human were established for 20 g of fly food i.e. 0.0014, 0.0028, 0.0042 and 0.0056 g per 20 g of diet. The PD flies were allowed to feed on it for 24 days before performing the assays. Results: The PD flies exposed to IMD showed increase in the life span and improvement in the activity. A significant dose dependent delay in the loss of climbing ability was observed in PD flies exposed to various doses of IMD. The exposure of PD flies to IMD showed a significant reduction in the oxidative stress and increase in the anti-oxidant enzymes compared to unexposed PD flies. The PD flies exposed to various doses of IMD showed a significant dose dependent increase in the activity of tyrosine hydroxylase as evident by immunohistochemistry. Conclusion: It is concluded that IMD is potent in reducing the PD symptoms being mimicked in the transgenic Drosophila.